1988
DOI: 10.1002/pola.1988.080260116
|View full text |Cite
|
Sign up to set email alerts
|

Formation and reaction of polyenesulfonic acid. I. Reaction of polyethylene films with SO3

Abstract: The surface of polyethylene (PE) film was sulfonated by reaction with gaseous SO3. The structure of the sulfonated PE films was determined on the basis of spectroscopic data such as IR, UV, and resonance Raman spectra. It was confirmed that a PE film and SO3 gave unsaturated sulfonic acids and that, as the reaction proceeded, the elimination of sulfurous acids took place to form sulfonic acids having highly conjugated CC unsaturated bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 7 publications
3
41
0
Order By: Relevance
“…When the sulfonation time exceeds 3 h, desulfonation reaction seems to be taking place while forming new functional groups containing elemental sulfur and oxygen atoms. It has been suggested that the formation of C¼ ¼C double bonds occurs by the desulfonation reaction following the formation of sulfonic acid [64][65][66] groups. Sulfonic acid bands around 1250-1000 cm À1 region indicate the presence of a weak peak, as a shoulder, located at about 1170 cm À1 (CAC chain stretching þ CH 3 rocking þ CH bending), clearly visible in the spectrum of sulfonated sample at 120 C for 30 min [ Fig.…”
Section: Assessment Of Ft-ir Spectroscopy Datamentioning
confidence: 99%
“…When the sulfonation time exceeds 3 h, desulfonation reaction seems to be taking place while forming new functional groups containing elemental sulfur and oxygen atoms. It has been suggested that the formation of C¼ ¼C double bonds occurs by the desulfonation reaction following the formation of sulfonic acid [64][65][66] groups. Sulfonic acid bands around 1250-1000 cm À1 region indicate the presence of a weak peak, as a shoulder, located at about 1170 cm À1 (CAC chain stretching þ CH 3 rocking þ CH bending), clearly visible in the spectrum of sulfonated sample at 120 C for 30 min [ Fig.…”
Section: Assessment Of Ft-ir Spectroscopy Datamentioning
confidence: 99%
“…17. Reaction mechanism of sulfuric acid with low density polyethylene, introducing sulfuric groups and carbon-to-carbon double bonds [86]. different mechanisms.…”
Section: Sulfuric Systemmentioning
confidence: 99%
“…Among polymers, surfaces of polyolefins have a low surface energy and are very inert, and various sulfonation methods have been tried to improve properties such as adhesion and wettability. Sulfonation includes several commonly used methods, e.g., treatments with gaseous SO 3 , [1,2] hot concentrated sulfuric acid, [3][4][5] and fuming sulfuric acid. [6][7][8] In addition, sulfonation using gaseous SO 2 has also been widely used for many years.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] It has been reported that SO 3 reacts with polyethylene films to yield sulfonic acid groups, although several reports on the reaction propose different sulfonation mechanisms. [1][2][3][4][5] We have proposed sulfonation mechanism of LDPE films with fuming sulfuric acid where SO 3 reacts with LDPE films to produce sulfonic acid groups via the formation of sultones. [17] Given that the generation of SO 3 occurs during photosulfonation, there might be a possibility of the production of sulfonic acid groups via the formation of sultones in the reaction between SO 3 and LDPE films.…”
Section: Introductionmentioning
confidence: 99%